P177 Adherence to a bowel cleansing regimen for pan-enteric capsule endoscopy in patients with suspected Crohn's disease and factors affecting the image quality. (27th May 2021) - Jacob Broder, B; Karina Winther, A; Jensen, M D
Abstract: Background: Pan-enteric capsule endoscopy (CE) is an attractive diagnostic approach in patients examined for Crohn's disease (CD). The current bowel cleansing regimen was developed for patients with suspected gastrointestinal neoplasia (polyps). Since the majority of patients with CD have diarrhoea, a reduced volume of bowel preparation may be sufficient for cleansing the colon. The aim of this study was to examine the adherence to the recommended bowel cleansing regimen in patients with suspected CD examined with pan-enteric CE and determine clinical factors affecting the image quality. Methods: Patients with clinically suspected CD were prospectively enrolled in a trial examining non-invasive modalities for diagnosing CD (http://ClinicalTrials.gov Identifier NCT03134586). All patients had a standardized work-up including medical history, physical examination, blood and stool samples and pan-enteric CE. CE was performed with the PillCam™ Crohn's capsule (Medtronic, Dublin, Ireland) after overnight fasting and bowel preparation with 2 + 2 litres of Polyethylene glycol (Moviprep®, PEG + ascorbic acid) and Sodium Phosphate booster as previously described by ESGE. Readers were blinded to the results of other examinations. The image quality was graded on a 4-point scale (poor, fair, good, excellent). A good or excellent image quality defined a diagnostic procedure. Results: The volume of ingested PEG was recorded in 59 patients (Table 1). The mean volume was 2.5 L (CI 2.3–2.8). 10 patients (17%) were able to drink all 4 L of PEG, and 44 patients (75%) ingested > 2 L. The image quality was poor, fair, good or excellent in 0%, 29.3%, 29.3% and 41.4%, respectively. The mean volume of PEG was 1.9 L (CI 1.4–2.4), 2.2 L (CI 1.8–2.7) and 3.2 L (CI 2.8–3.5) in patients with a fair, good or excellent image quality ( P < 0, 001, Figure 1). In a regression analysis including multiple clinical variables, only the volume of ingested PEG was associated with the obtained image quality (Spearman's rho = 0.52; P < 0.001). Stool consistency, number of bowel movements, diagnosis of inflammatory bowel disease (IBD) or the degree of inflammation did not affect the image quality. The diagnostic yield was equal in patients with a diagnostic or non-diagnostic image quality (44% and 44%, respectively). The capsule was excreted in 53 patients (90%), and the analysis was not able to determine factors affecting the completion rate. Conclusion: In patients examined with pan-enteric CE for suspected CD, the ingested volume of PEG is the major factor affecting the image quality. However, only few patients are able to ingest the recommended volume. Future research should determine the optimal bowel cleansing regimen for patients examined for IBD.